Analisis Tasybih dalam Surah al-Insyiqaq - Nur Syahvika (Asian Journal of Islamic Studies and Da'wah, 2026)
This study was motivated by the importance of examining the language style of the Al-Qur’an in deepening the understanding of the meaning of its verses, particularly through the analysis of tasybih in the study of balaghah. This study aims to analyze the use of tasybih in Surah Al-Insyiqaq as part of the language style of the Al-Qur’an. This study used a literature review method with a focus on analyzing the verses in Surah Al-Insyiqaq that contain elements of tasybih. This study includes the identification of the components of tasybih, such as musyabbah, musyabbah bih, and adat tasybih, as well as the types and purposes of their use in the surah. The results showed that tasybih in Surah Al-Insyiqaq functions to depict natural phenomena and prophetic events symbolically, thereby facilitating readers’ understanding while also generating an emotional impact. This study concludes that the use of tasybih in Surah Al-Insyiqaq plays an important role in clarifying the meaning of the verses and strengthening the message conveyed, as well as contributing to the development of balaghah and to a deeper understanding of the meanings of the Al-Qur’an.